2016
DOI: 10.1007/s00439-016-1633-2
|View full text |Cite
|
Sign up to set email alerts
|

A genome-wide association study of pulmonary tuberculosis in Morocco

Abstract: Although epidemiological evidence suggests a human genetic basis of pulmonary tuberculosis (PTB) susceptibility, the identification of specific genes and alleles influencing PTB risk has proven to be difficult. Previous genome-wide association (GWA) studies have identified only three novel loci with modest effect sizes in sub-Saharan African and Russian populations. We performed a GWA study of 550,352 autosomal SNPs in a family-based discovery Moroccan sample (on the full population and on the subset with PTB … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 43 publications
1
48
1
Order By: Relevance
“…However, the power to detect a common variant with an odds ratio of 2 was 98%. Validation of these results in other case-control cohorts as well as the inclusion of recent GWAS results [5,12,14] is desirable, but complicated by the lack of available TB case-control cohorts with a similar genetic structure to that of the SAC population. In addition, since there was a priori evidence for an association, replication is arguably not necessary as this study attempted to fine-map the potential causal variants in loci identified by previous TB GWAS.…”
Section: Discussionmentioning
confidence: 99%
“…However, the power to detect a common variant with an odds ratio of 2 was 98%. Validation of these results in other case-control cohorts as well as the inclusion of recent GWAS results [5,12,14] is desirable, but complicated by the lack of available TB case-control cohorts with a similar genetic structure to that of the SAC population. In addition, since there was a priori evidence for an association, replication is arguably not necessary as this study attempted to fine-map the potential causal variants in loci identified by previous TB GWAS.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that ADA2 might be important for the regulation of the innate immune responses against MTB infection. Interestingly a recent genome wide association studies (GWAS) failed to identify ADA2 as a common susceptibility locus for MTB infection . However, it is prudent to say that GWAS typically interrogate polymorphisms and that rare variants may be overlooked.…”
Section: The Human Adenosine Deaminase Enzymes: a Historical Perspectivementioning
confidence: 99%
“…Interestingly a recent genome wide association studies (GWAS) failed to identify ADA2 as a common susceptibility locus for MTB infection. 33 However, it is prudent to say that GWAS typically interrogate polymorphisms and that rare variants may be overlooked. On the viral side, plasma ADA2 has been used as a marker for HIV-1 seroconversion and HTLV infection.…”
Section: The Discovery Of Ada2 and The Genes That Encode It In Invementioning
confidence: 99%
“…A case-control GWAS in a Russian population replicated the chromosome 11 locus, but not the chromosome 18 locus; it also detected significant association with the ASAP1 gene [44]. While a GWAS conducted in a Moroccan population did not detect any genome-wide significant associations, it replicated results from chromosomes 11 and 18 at a nominal significance (p<0.05) [45]. A GWAS in an Indonesian population did not detect any loci that were significant after multiple testing correction, although it did identify suggestively associated loci involved in immune signaling; the previous GWAS associations were not explicitly tested in this study [46].…”
Section: Previous Genetic Studies Of Tbmentioning
confidence: 99%